Coach education effectiveness: from a coach perspective - Yusoff, Nur Suzyani Efazila (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
The coach education programs in Malaysia play important role in certification of the coaches. 6 coaches were involve in this studies, 5 of them was male and 1 female. These studies used semi-structure interview to collection of data especially their experience when they are taking National Coach Certification Scheme. This National Coach Certification Scheme was provided to all of people who want to be a coaches', there have 3 level for every component which is include sport science component, sport specific component and practical. The coaches who get the certificate for every level with combine sport science component, sport specific and pass their practical will get the licence of National Coaching Licence Scheme and will get the benefit like salaries from National Sport Council. These studies were followed the theory from a Moon's (2004) generic view of learning. After a coaches get certificate, in every 2 years, they must follow continuous coach education programs to renew their licence. This programs is important for all coaches who already certificated. Either they a novice coaches or elite coaches. This researched were explore the coaches experience when they a taking National Coaching Certification Coach and Continuous Coach Education.